A colorimetric pH indicators and boronic acids ensemble array for quantitative sugar analysis - Ghosh, Krishna Kanta; Yap, Eunice; Kim, Hanjo; Lee, Jun-Seok; Chang, Young-Tae (ROYAL SOC CHEMISTRY, 2011)
The colorimetric response patterns of pH indicators and boronic acids ensemble array were used to analyze serial concentrations of mono-, disaccharides quantitatively. Furthermore, this ensemble array was successfully applied to quantify the sugar content in clinically used saline solutions.
Keywords: SENSOR ARRAY; BIPYRIDINIUM SALTS; SENSING ENSEMBLE; WATER; IDENTIFICATION; RECEPTORS; DESIGN